Illocutionary Speech Acts of Cristiano Ronaldo and Their Influence on His Personality in Football - Abdullah, Muhammad Usamah Syamil; Ruminda, Ruminda; Yatmikasari, Ika (Universitas Negeri Makassar, 2025)
Abstract. The purpose of this research is to examine Cristiano Ronaldo's illocutionary speech acts and how they affect his personality in the context of football. The study uses a descriptive qualitative methodology to analyze transcripts of ten interviews and podcasts covering Ronaldo's career, from his early days at Manchester United to his most recent appearances. The analysis employs Searle's (1969) classification of illocutionary acts—representatives, directives, commissives, declarative, and expressive—alongside Sperber and Wilson's (1996) Relevance Theory and McCrae's (1999) Five-Factor Personality Model. The results show that Cristiano Ronaldo used 242 illocutionary speech acts, with 104 representative speech acts accounting for 43% of the total. These acts expressed declarative statements about his abilities and self-confidence, followed by 55 expressives (23%), 40 commissives (16%), 36 directives (15%), and 7 declaratives (3%). These patterns reflect key personality traits: high Openness (articulating beliefs candidly), Conscientiousness (goal-oriented commitments), extraversion (emotional engagement with audiences), moderate Agreeableness (collaborative directives), and low Neuroticism (stable emotional expressions). The study concludes that Cristiano Ronaldo's strategic use of speech acts not only shapes his public persona as a disciplined and inspirational figure but also corresponds to the psychological characteristics that support his professional success and cultural influence. This integration of pragmatic and psycholinguistic frameworks provides new insights into how linguistic behaviour reflects and reinforces personality in high-stakes situations. Keywords: Cristiano Ronaldo; interviews; illocutionary acts; personality traits; psycho-pragmatics